2001
DOI: 10.1007/s003830100590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low fat diet on lipid absorption and fatty-acid transport following bowel resection

Abstract: Low-fat diets (LFD) are used extensively in many different clinical conditions. However, the effect of this diet on lipid absorption and cellular long-chain fatty-acid (LCFA) transport is unknown. Fatty-acid translocase (FAT), the rat homologue of human CD36, is one of several LCFA plasma-membrane transport proteins that may play an important role in intestinal lipid uptake. The purpose of this study was to investigate the effects of a LFD on intestinal expression of FAT/CD36, enterocyte fatty-acid transport, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…A previous study has found that rats given a low fat diet with 3% kcal/fat after SBR were found to have decreased body weight, mucosal weight, and attenuated villus height/proliferation/apoptosis in the ileum when compared to normal chow. 5, 6 However, our results reveal that at least 10% kcal fat as in LFD is adequate to demonstrate adaptive changes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A previous study has found that rats given a low fat diet with 3% kcal/fat after SBR were found to have decreased body weight, mucosal weight, and attenuated villus height/proliferation/apoptosis in the ileum when compared to normal chow. 5, 6 However, our results reveal that at least 10% kcal fat as in LFD is adequate to demonstrate adaptive changes.…”
Section: Discussionmentioning
confidence: 55%
“…4 However, the mechanism for high fat induced intestinal adaptation remains unknown. While it has been suggested that a low fat diet is detrimental to adaptation 5, 6 , it is unknown how much fat is needed to generate an augmented adaptation response. Additionally, it is unknown what kind of fat produces the optimal response after resection.…”
Section: Introductionmentioning
confidence: 99%
“…A lowfat diet affected adaptive responses by an inhibition of enterocyte proliferation and did so independent of enterocyte apoptosis [18]. In another investigation [19], we reported that depletion of dietary fat inhibited cellular and molecular mechanisms of LCFA absorption by isolated enterocytes in the same model. This was associated with a decrease in LCFA plasma-membrane transport protein fatty-acid translocase (FAT) (the rat homologue of human CD36) and with a decrease in isolated enterocyte [3H]-oleate uptake as measured by an established cellular LCFA transport assay [19].…”
Section: Adaptation and Nutrientsmentioning
confidence: 95%
“…L'expression intestinale du CD36 est etroitement corr el ee avec la teneur en lipides du r egime. Alors qu'un r egime pauvre en lipides diminue son expression (Sukhotnik et al, 2001), un r egime hyperlipidique chronique l'induit fortement (Poirier et al, 1996). Cependant, a la diff erence de l'adipocyte et du myocyte, la contribution significative de CD36 dans le captage ent erocytaire des AGLC est mise en doute.…”
Section: Cd36unclassified